2015
DOI: 10.4049/jimmunol.1402665
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Adenosine Inhibits sPLA2-IIA–Mediated Host Killing in the Airways

Abstract: Staphylococcus aureus is a common cause of bacterial infections in respiratory diseases. It secretes molecules to dampen host immunity, and the recently identified adenosine is one of these molecules. The type IIA secretory phospholipase A2 (sPLA2-IIA) is a host protein endowed with antibacterial properties, especially against Gram-positive bacteria such as S. aureus. However, the role of adenosine in sPLA2-IIA–mediated S. aureus killing by host is still unknown. The present studies showed that the S. aureus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…The chronicity of specific infections (27), their interactions with human host defenses, and their clinical outcomes have been studied previously (28). Microbial species-to-species interactions among pathogens similar to those found in the CF airway have been studied in various in vitro and nonhuman in vivo model systems (17,18,(29)(30)(31)(32)(33)(34)(35)(36)(37), and the clinical effects of the combination of P. aeruginosa and MSSA have been explored (38), but interspecies microbial interactions in the CF airway have been minimally explored, and recent calls to expand this knowledge base remain outstanding (16,39).…”
Section: Discussionmentioning
confidence: 99%
“…The chronicity of specific infections (27), their interactions with human host defenses, and their clinical outcomes have been studied previously (28). Microbial species-to-species interactions among pathogens similar to those found in the CF airway have been studied in various in vitro and nonhuman in vivo model systems (17,18,(29)(30)(31)(32)(33)(34)(35)(36)(37), and the clinical effects of the combination of P. aeruginosa and MSSA have been explored (38), but interspecies microbial interactions in the CF airway have been minimally explored, and recent calls to expand this knowledge base remain outstanding (16,39).…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive effect of adenosine requires perception by host cells, which is mediated by four distinct receptors A1, A2A, A2B and A3, all of which can be expressed by macrophages among other cell types [ 223 , 224 ]. Importantly, in the context of the macrophage, alveolar macrophages exposed to adenosine, or AdsA competent S. aureus , demonstrate decreased production of the type 2 secretory phospholipase A2 and have a reduced capacity to phagocytose staphylococci in the airways of experimental animals [ 225 ]. Thus macrophages are indeed sensitive to the function of AdsA, which is a versatile enzyme and virulence determinant of S. aureus that can perturb macrophage function through production of adenosine and/or the induction of apoptosis.…”
Section: Extracellular Intoxication Of Phagocytesmentioning
confidence: 99%
“…Our study also highlights an important role for hGIIA in the humoral immune response against E. faecium. While other groups reported that high concentrations of hGIIA (produced locally in lungs and tears [40,41] or in serum under septic shock conditions [42,43]) could disrupt certain Gram-positive bacteria, its importance in normal serum or plasma has not been recognized in physiological concentrations, besides its activity against Listeria monocytogenes (34). We observed restoration of killing of commensal E. faecium when recombinant hGIIA was added in physiological concentrations in heat-inactivated human serum.…”
Section: Discussionmentioning
confidence: 52%